Collateral damage? - Cabral, Sónia (2022)
The increasing range and quality of China's exports is a major development internationally with potentially far-reaching effects. In this paper, on top of the direct labour market effects of imports from China studied in previous research, we also measure the indirect effects stemming from increased export competition in third markets. Our findings, based on matched employer–employee data of Portugal covering the period 1991–2008, indicate that workers’ earnings and employment are significantly negatively affected by China's competition, but only through the indirect ‘market-stealing’ channel. In contrast to earlier evidence, the direct effects of Chinese imports are mostly non-significant. The results are robust to a number of checks and also highlight particular groups more affected by indirect competition, including women, older and less educated workers, and workers in larger, older and domestic firms.